Randomized trial of medical compression stockings versus two-layer short-stretch bandaging in the management of venous leg ulcers - Taradaj, J.; Franek, A.; Brzezinska-Wcislo, L.; Blaszczak, E.; Polak, A. (Phlebologie, 2009)
A prospective randomized clinical trial was undertaken to compare a medical compression stockings with two-layer short-stretch bandaging in the management of venous leg ulcers. Study endpoints were number of completely healed wounds and the clinical parameters predicting the outcome. Patients, methods: Eighty patients with venous leg ulcers were included in this study, and ultimately allocated into two comparative groups. Group A consisted of 40 patients (25 women, 15 men). They were treated with the compression stockings (25–32 mmHg) and drug therapy. Group B consisted of 40 patients (22 women, 18 men). They were treated with the short-stretch bandages (30–40 mmHg) and drug therapy, administered identically as in group A. Results: Within two months the 15/40 (37.50%) patients in group A and 5/40 (12.50%) in group B were healed completely (p = 0.01). For patients with isolated superficial reflux, the healing rates at two months were 45.45% (10/22 healed) in group A and 18.18% (4/22 healed) in group B (p = 0.01). For patients with superficial plus deep reflux, the healing rates were 27.77% (5/18 healed) in group A and 5.55% (1/18 healed) in group B (p = 0.002). Comparison of relative change of the total surface area (61.55% in group A vs. 23.66% in group B), length (41.67% in group A vs. 27.99% in group B), width (46.16% in group A vs. 29.33% in group B), and volume (82.03% in group A vs. 40.01% in group B) demonstrated difference (p = 0.002 in all comparisons) in favour of group A. Conclusion: The medical compression stockings are extremely useful therapy in enhancement of venous leg ulcer healing (both for patients with superficial and for patients who had superficial plus deep reflux). Bandages are less effective (especially for patients with superficial plus deep reflux, where the efficiency compared to the stockings of applied compression appeared dramatically low). These findings require confirmation in other randomized clinical trials with long term results.
Keywords: Medical compression stockings; venous leg ulcers